High Power Factor and Enhanced Thermoelectric Performance in Sc and Bi Codoped GeTe: Insights into the Hidden Role of Rhombohedral Distortion Degree. Issue 42 (27th September 2020) - Liu, Zihang; Gao, Weihong; Zhang, Wenhao; Sato, Naoki; Guo, Quansheng; Mori, Takao
Abstract: Modification of crystal symmetry induced by chemical doping or alloying is well known to optimize the charge carrier transport properties in thermoelectric materials. Historically, the altered defect chemistry of the targeted materials, however, has long been neglected or underestimated, which may, in turn, favorably or adversely affect the thermoelectric properties. Herein, using a case study of thermoelectric GeTe, first, the hidden role of rhombohedral distortion degree on the Ge‐vacancy formation energy is theoretically unraveled, and it is experimentally found that Sc and Bi codoping realize a superior thermoelectric performance. Density functional theory calculations demonstrate that the distorted rhombohedral lattice closer to cubic would unexpectedly induce the significantly decreased formation energy of Ge vacancies, resulting in the spontaneous formation of higher‐concentration Ge vacancies. Sc doping is found to be the most effective dopant to reduce the carrier concentration without obviously affecting the rhombohedral distortion degree, leading to the realization of a record‐high power factor. Benefiting from the suppressed thermal conductivity by further Bi doping, an ultrahigh average ZT ≈1.2 from 300 to 723 K is achieved. These discoveries provide new insights into the relationship between crystal symmetry and defect chemistry, and also promote GeTe materials for future thermoelectric applications. Abstract : The relationship between crystal symmetry and defect chemistry in GeTe is clarified, in which a rhombohedral lattice closer to its cubic counterpart leads to the decreased formation energy of Ge vacancies. Sc doping is demonstrated to be effective in improving the power factor, due to a dual role that efficiently reduces the carrier concentration without obviously affecting the rhombohedral distortion degree.